2012
DOI: 10.1108/01443571211250112
|View full text |Cite
|
Sign up to set email alerts
|

SKU classification: a literature review and conceptual framework

Abstract: Purpose -Stock Keeping Unit (SKU) classifications are widely used in the field of production and operations management. Although many theoretical and practical examples of classifications exist, there are no overviews of the current literature, and general guidelines are lacking with respect to method selection. The purpose of this paper is to systematically synthesise the earlier work in this area, and to conceptualise and discuss the factors that influence the choice of a specific SKU classification. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 71 publications
1
50
0
11
Order By: Relevance
“…When classifying inventory, two questions need to be addressed: (1) How many classes must be used? and (2) How do we determine the borders between these classes (Van Kampen, Akkerman, & Pieter van Donk, 2012)?…”
Section: Introductionmentioning
confidence: 99%
“…When classifying inventory, two questions need to be addressed: (1) How many classes must be used? and (2) How do we determine the borders between these classes (Van Kampen, Akkerman, & Pieter van Donk, 2012)?…”
Section: Introductionmentioning
confidence: 99%
“…In their study, a multi-criteria ABC analysis was conducted with the TOPSIS method. From the studies of Kampen, Akkerman & Donk [19] and Praveen, Jay & Venkataram [20], readers can find the literature reviews of different algorithms used for inventory classification.…”
mentioning
confidence: 99%
“…The control with a lower level may be applied to B and C goods. Van Kampen et al (2012) found that the classification of goods has been carried out in various industries. Meanwhile, Shen (2015) and Teunter et al (2010) stated that the level of service is one of the determinants of cost savings and quality of service associated with inventory.…”
Section: Introductionmentioning
confidence: 99%